Consistent altered internal capsule white matter microstructure in insomnia disorder. Issue 8 (3rd March 2020) - Bresser, Tom; Foster-Dingley, Jessica C; Wassing, Rick; Leerssen, Jeanne; Ramautar, Jennifer R; Stoffers, Diederick; Lakbila-Kamal, Oti; van den Heuvel, Martijn; van Someren, Eus J W
Abstract: Study Objectives: Suggested neural correlates of insomnia disorder have been hard to replicate. Even the most consistent finding, altered white matter microstructure in the anterior limb of the internal capsule, is based on handful studies. The urge for replicable targets to understand the underlying mechanisms of insomnia made us study white matter fractional anisotropy (FA) across three samples of cases and controls. Methods: 3-Tesla MRI diffusion tensor imaging data of three independent samples were combined for analysis, resulting in n = 137 participants, of whom 73 were diagnosed with insomnia disorder and 64 were matched controls without sleep complaints. Insomnia severity was measured with the Insomnia Severity Index (ISI). White matter microstructure was assessed with FA. White matter tracts were skeletonized and analyzed using tract-based spatial statistics. We performed a region-of-interest analysis using linear mixed-effect models to evaluate case–control differences in internal capsule FA as well as associations between internal capsule FA and insomnia severity. Results: FA in the right limb of the anterior internal capsule was lower in insomnia disorder than in controls (β = −9.76e −3 ; SE = 4.17e −3, p = .034). In the entire sample, a higher ISI score was associated with a lower FA value of the right internal capsule (β = −8.05e−  4 FA/ISI point, SE = 2.60e−  4, p = .008). Ancillary whole brain voxel-wise analyses showed no significant group difference or association with insomnia severity after correction for multiple comparisons. Conclusions: The internal capsule shows small but consistent insomnia-related alterations. The findings support a circuit-based approach to underlying mechanisms since this tract connects many brain areas previously implicated in insomnia.